2021
DOI: 10.1186/s40494-021-00495-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of passive samplers for monitoring of acetic and formic acid in museum environments

Abstract: Acetic acid and formic acid are volatile pollutants leading to degradation of some heritage materials. They are usually determined in museum environments with various types of passive samplers. In this work, SKC UMEx 200 passive samplers, originally intended for sampling of $$\hbox {NO}_{2}$$ NO 2 and $$\hbox {SO}_{2}$$ SO 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The formation of organic acids is observed primarily in museum exhibits made of wood. These acids emitted from wood have a corrosive effect on exposed exhibits [ 66 , 67 , 68 ]. The study by Barbero-López et al [ 69 ] examines the in vitro antifungal and wood preservative activities of acetic, formic, and propionic acids against the wood decay fungi Coniophora puteana, Rhodonia (Poria) placenta , Gloeophyllum trabeum , and Trametes versicolor .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of organic acids is observed primarily in museum exhibits made of wood. These acids emitted from wood have a corrosive effect on exposed exhibits [ 66 , 67 , 68 ]. The study by Barbero-López et al [ 69 ] examines the in vitro antifungal and wood preservative activities of acetic, formic, and propionic acids against the wood decay fungi Coniophora puteana, Rhodonia (Poria) placenta , Gloeophyllum trabeum , and Trametes versicolor .…”
Section: Resultsmentioning
confidence: 99%
“…The sample, e.g., collected on SPME, is introduced directly, or else extracted first, e.g., from sorbent tubes, where extraction proceeds thermally with solvents. Liquid extracts can also be analysed using high-performance liquid chromatography (HPLC), commonly used for the analysis of aldehydes [108,109], or with ion chromatography (IC) for the analysis of low-molecular-weight acids, such as formic and acetic acid [110,111].…”
Section: Analysis Of Volatilesmentioning
confidence: 99%
“…Several research studies have investigated the most common indoor volatiles and the associated risks to collections [4,111,114]. In addition, studies have shown that some toxic or otherwise hazardous compounds found in museum air can affect human health (depending on the exposure time, exposure level, concentration and the person's medical condition and age), which emphasizes the need to define limits for indoor pollutant concentrations in heritage environments [2,115].…”
Section: Museum Guidelinesmentioning
confidence: 99%
“…Preventive conservation of cultural heritage objects is the focus of recent studies resulting in the development of new materials to provide art objects with a protective layer against deterioration sources, such as ultraviolet (UV) light, oxygen, moisture, and corrosive agents. Moreover, these studies allow for the monitoring of volatile organic compounds (VOCs) connected to corrosion, cross-linking, or discoloration of exposed artworks in museums and allow for the design of smart storage of museum artifacts, providing microclimate monitoring . In this context, it makes sense to focus on synthetic materials, specifically acrylic paints, because their stability and response to aging depend on various factors.…”
Section: Introductionmentioning
confidence: 99%